2021
DOI: 10.3390/genes12111802
|View full text |Cite
|
Sign up to set email alerts
|

Age at Glaucoma Diagnosis in Germline Myocilin Mutation Patients: Associations with Polymorphisms in Protein Stabilities

Abstract: Glaucoma is the leading cause of irreversible blindness worldwide, with elevated intraocular pressure (IOP) as the only known modifiable risk factor. Trabecular meshwork (TM)-inducible myocilin (the MYOC gene) was the first to be identified and linked to juvenile and primary open-angle glaucoma. It has been suggested that mutations in the MYOC gene and the aggregation of mutant myocilin in the endoplasmic reticulum (ER) of TM may cause ER stress, resulting in a reduced outflow of aqueous humor and an increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 82 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…In addition, there is an age at diagnosis for variants now considered benign because individuals harboring myocilin polymorphisms can still develop glaucoma even if the relationship is not causal. Nevertheless, in our early biophysical study of the OLF domain ( Burns et al, 2011 ), a weak positive linear correlation between OLF variant T m and age at diagnosis was suggested, and this apparent relationship was repeated in a recent literature review by others ( Tanji et al, 2021 ). Upon plotting the new variants characterized here alongside all variants for which clinical and experimental stability data are available, no convincing trendline was observed, however ( Fig.…”
Section: Resultsmentioning
confidence: 65%
“…In addition, there is an age at diagnosis for variants now considered benign because individuals harboring myocilin polymorphisms can still develop glaucoma even if the relationship is not causal. Nevertheless, in our early biophysical study of the OLF domain ( Burns et al, 2011 ), a weak positive linear correlation between OLF variant T m and age at diagnosis was suggested, and this apparent relationship was repeated in a recent literature review by others ( Tanji et al, 2021 ). Upon plotting the new variants characterized here alongside all variants for which clinical and experimental stability data are available, no convincing trendline was observed, however ( Fig.…”
Section: Resultsmentioning
confidence: 65%
“…For example, the first pathogenic mutation for primary open-angle glaucoma has been identified in the myocilin gene [ 36 ]. The aggregation of mutant myocilin can lead to a severe decline in TM cellularity due to endoplasmic reticulum stress [ 37 , 38 ]. To this end, it is very important to investigate how damage occurs in different TM subpopulations.…”
Section: Discussionmentioning
confidence: 99%
“…Myocilin is mainly expressed in TM cell, and excessively accumulated in ER when MYOC is mutated or overexpressed, which may trigger or disrupt protein clearance mechanisms including ER-associated degradation (ERAD) and autophagy ( Kasetti et al, 2021 ; Tanji et al, 2021 ). However, previous studies only reported the difference between WT-MYOC and mutated-MYOC (Y437H, G364V, Q368X, etc ), ignoring the alteration induced by MYOC neutral polymorphisms.…”
Section: Discussionmentioning
confidence: 99%